Gestión administrativa-financiera y su incidencia en el presupuesto de la empresa pública municipal terminal terrestre, tránsito y seguridad vial de la ciudad de Babahoyo periodo 2017-2018 - Fernández Santillán, Andrea Ximena (2018)
This research profile addresses the results of a cross-sectional field study carried out between January 2017 and November 2018 on the impact of administrative-financial management and its influence on the use of the budget of the Municipal Public Company Terrestrial Terminal, Traffic and Road Safety of the city of Babahoyo, for which it is considered convenient to assume as a central objective to determine the processes developed in the financial administrative management of the Municipal Public Company Terminal Terrestre, Transit and Road Safety of the city of Babahoyo. For data collection has been used, methods and techniques of scientific research, such as the method of observation, the technique of survey and interview. The main findings derived from the application of the method and techniques described above were achieved in obtaining an initial diagnosis that revealed the shortcomings surrounding the achievement of the company's objectives in the short, medium and long term, in indicators such as the management and performance measures to evaluate the institutional or sectoral management and the individual performance of its servers, as well as the levels of compliance with the law, specific norms issued by State institutions, or regulations of a generally mandatory nature issued by competent authorities, including those related to the performance of each position, among others. Obtaining conclusions that must be taken into account by the pertinent authorities so that they propitiate the solution of the assumed scientific problem and consequently the solution of programmed work is accepted. KEY WORDS: Administrative management, Financial management. Budget, Public company